Post-Denosumab-Treated Giant Cell Tumor of Bone: A Retrospective Histomorphological and Immunohistochemical Study - Kamble, Anvesh; Hui, Monalisa; Rao, K. Nageshwara; Ramakrishna, N.; Chandrasekhar, P.; Uppin, Shantveer G.; Sadashivudu, G. (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Giant cell tumors of bone (GCTBs) are treated with surgery with or without local adjuvants. Denosumab is a human monoclonal antibody that has recently emerged to be effective in treating unresectable and recurrent GCTBs.Objective In this study, we analyzed the histomorphological changes in GCTB following treatment with denosumab. The expression of histone mutation H3.3G34W by immunohistochemistry (IHC) using mutant specific antibody was also determined.Materials and Methods Of the total 109 GCTBs encountered during the study period, 14 cases with neoadjuvant denosumab therapy were analyzed retrospectively. The post-treatment changes on histopathology were examined on routine hematoxylin and eosin-stained sections. IHC was done using antihistone H3.3G34 antibodies. Statistical analysis was limited to descriptive statistics. No hypothesis testing was performed.Results All these cases except three showed fibrosis with areas of hyalinization, prominent newly formed woven bone along with spindle cells in short fascicles and storiform pattern. There was complete absence and marked reduction in osteoclast-like giant cells in six and five patients, respectively. Only three patients showed a substantial amount of residual osteoclast-like giant cells. IHC with antihistone H3.3G34W antibody showed unequivocal nuclear positivity in the mononuclear cells in nine cases. The mononuclear cells rimming and entrapped within the woven bone were also positive on IHC. The spindle cells in the benign fibrous histiocytoma-like areas and septa of aneurysmal bone cyst-like areas also retained nuclear staining.Conclusion Awareness of post-denosumab-related histopathological changes are necessary to avoid misdiagnosis as fibroosseous lesion and low-grade central osteosarcoma. Expression of mutant-specific H3.3 G34W antibody suggests that the neoplastic stromal cells are largely retained after denosumab therapy. The positive staining of cells both within and those rimming the newly formed woven bone point toward osteoblastic phenotype of the neoplastic stromal cells.
Keywords: giant cells; denosumab therapy; histomorphological changes; antihistone antibody; immunohistochemistry